EFEKTIVITAS PELATIHAN SELF MANAGEMENT UNTUK MENINGKATKAN KEBAHAGIAAN PEKERJA SOSIAL DI LEMBAGA SWADAYA MASYARAKAT (LSM) YANG MENANGANI KASUS ANAK - Agustina Engry; Tri Kurniati Ambarini (EXPERIENTIA : Jurnal Psikologi Indonesia, 2019)
The purpose of this research is to find out the effectiveness of self management training to increase happinesss on social workers that work in children social organization. This study used a quasi experimental research with seven social workers from three different Children Social Organization. The type of quasi experimental designs is single group pretest posttest design. Instrument that used is The Oxford Happiness Questionnaire from Argyle and Hills (2001) that has adapted to bahasa Indonesia. Data analysis used Wilcoxon Signed Rank Test with sig 0,075 that means there is not a significant difference happiness score before and after self management training given.